Breast cancer in South Asia: a Bangladeshi perspective - Hossain, Mohammad Sorowar; Ferdous, Shameema; E. Karim-Kos, Henrike (© 2014 Elsevier Ltd., 2017)
This article was published in Cancer Epidemiology [© 2014 Elsevier Ltd.] and the definite version is available at: http://www.sciencedirect.com/science/article/pii/S1877782114001441